Candidate and party affective polarization in U.S. presidential elections: The person-negativity bias?. (June 2021) - Bolsen, Toby; Thornton, Judd R.
Abstract: We investigate the degree of affective polarization in presidential election years toward the two major parties and their nominees. Notwithstanding studies which show that individuating information about an out-group member can generate a person-positivity bias, we demonstrate a person-negativity bias directed at out-party candidates at least for some. We motivate and test two hypotheses: first, we expect more sophisticated partisans to display a greater difference in their feelings towards specific candidates compared to evaluations of the parties themselves; second, we anticipate sophisticated partisans will exhibit a person-negativity bias toward out-party candidates and a person-positivity bias toward in-party candidates. The results accentuate the conditional nature of the person-positivity bias and shed light on how political sophistication is linked to affective polarization.